Cylindrocladium scoparium in relation to leaf rot disease of coconut - M. GUNASEKARAN, N. SRINIVASAN and (Indian Phytopathology, 2002)
Leaf rot disease of coconut is a major disease, found super-imposed on over 60 per cent of root/ wilt affected palms in Kerala. The early symptoms of the disease are usually manifested in spindle leaves as necrotic lesions, spots etc. which develop into extensive rotting of tender tissues, under favourable conditions. Fungal etiology of the disease has been established and species composition of the leaf rot complex elucidated. During isolations of fungi from leaf rot, a hyphomycetous fungus identified as Cylindrocladium scoparium Morgan, was cultured in vitro from infected tissues. Pathogenic association of C. scoparium with certain plant diseases assumes serious concern. Hence, identification of the fungus and its relation with leaf rot, based on pathogenicity tests are presented.